Islamic Religious Education Efforts for Narcotics Addicts at the Rumah Rahayu Rehabilitation Foundation - Khair, Fathul; Agustiansyah, Tri Aan; Kusdiana, Asep Nugraha; Ratri, Maya Masita; Hidayati, Yuli; Prisandy, Lucky (Journal of English Language and Education, 2026)
This study aims to analyze the efforts of Islamic Religious Education in fostering and rehabilitating clients of narcotics addicts at the Rumah Rahayu Rehabilitation Foundation in Pontianak City. The problem of narcotics abuse not only impacts the physical and psychological aspects, but also results in spiritual and moral crises in individuals. Therefore, a religious approach, especially through Islamic Religious Education, is important in the process of recovery and reformation of a person of faith and piety. The research method used is qualitative with a descriptive approach. Data was collected through observations, interviews with Foundation administrators, counselors who also served as spiritual advisors and rehabilitation clients, and documentation of religious activities carried out in rehabilitation facilities. Data analysis was carried out inducively to describe the form and results of the implementation of Islamic religious education for narcotics addict clients. The results of the study show that the implementation of Islamic Religious Education at the Rumah Rahayu Rehabilitation Foundation includes congregational prayer activities 5 (five) times, routine recitation every Friday night, praying together before meals, memorizing short surah for those who can afford it. The activity was led by a counselor who doubled as a spiritual guide. These activities have been proven to help clients in fostering spiritual awareness, a sense of responsibility towards themselves, and motivation to abandon drug abuse behaviors. In conclusion, Islamic Religious Education has a significant role in the rehabilitation process of narcotics addicts, especially in reshaping the religious, moral, and social values of clients. The support of counselors and a conducive environment is an important factor in the success of the foundation's religious development program.